Poland’s higher education in economics: current state and outlook - Jurek, Witold (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
My presentation is divided into three parts exploring the changes in the higher education system in Poland after the systemic transformation, the changes in the system of higher education of economics during this period, and the conditions of the prospective activity of higher education economic institutions in the foreseeable future. Basically, I shall disregard internal factors while focusing on selected external factors that have been shaping Poland's academic education in economics, and - I believe - will continue to do so in the future. Please forgive me that some questions will be tackled briefly, in note form, and the generalizing conclusions, as the restricted time of the presentation does not allow more detailed treatment
Argumenta Oeconomica, 2013, Nr 1 (30), s. 5-12
Keywords: higher education; economic science; economic knowledge; szkolnictwo wyższe; nauki ekonomiczne; wiedza ekonomiczna